Specifying the Concept of Sadness in the Holy Qur'an: A Qualitative Analysis - Ezatollah Kalantari Khandani; Mehdi Mohammadi Nia; Masoud Akbarizadeh (Kerman University of Medical Sciences, 2020)
Introduction: Sadness is the most important natural emotion of human beings. The feeling of sadness is experienced throughout the private and public life of mankind. Therefore, the present study aimed to explain the concept of grief by referring to the Holy Qur'an. Methods: This study was conducted through qualitative content analysis method. From among the Qur'anic concepts relevant to sadness, which were collected from the whole Qur'an, 60 concepts were selected via targeted sampling for analysis. Results: From the analysis of the Qur'anic concepts of sadness, six main categories including "physiology", "psychology", "emotion", "spirituality", "remedy", and "consequences" emerged. Conclusion: According to the results, it can be inferred that sadness in the Holy Qur'an is a multidimensional concept and various structures have been used to explain it. That is why all human beings, with respect to the high incidence of depression and sadness, have to pay more attention to this concept, and for being treated, they must accept that all things in the universe occur under God's lordship.